Effects of Acetyl-L-Carnitine Administration on Auditory Evoked Potentials in Rats Exposed to Chronic Ethanol - Er, Hakan; Kantar, Deniz; Acun, Alev Duygu; Gemici, Ayşegül; Derin, Narin; Ercan Kelek, Sevim (International Journal of Computational and Experimental Science and Engineering, 2024)
These days, one of the biggest issues facing public health is chronic alcohol consumption. Prolonged alcohol intake has been associated with a number of illnesses, including pancreatitis, cerebrovascular illnesses, and liver damage. It is known that the endogenous molecule acetyl-L-carnitine (ALCAR) has neuroprotective properties. The objective of this study was to examine the impact of ALCAR on auditory evoked potentials (AEP) in a model of chronic alcoholism in rats. Four groups (n = 10) were randomly formed from 40 three-month-old albino Wistar rats: Sham (Sh), chronic ethanol (CE), ALCAR administered (ALCAR), and chronic ethanol+ALCAR (CE+ALCAR). The rats were administered either distilled water, ethanol, ALCAR, or ethanol+ALCAR via gavage for a duration of 4 weeks. AEP recordings were acquired from each rat upon the conclusion of the experiment period. The amplitudes of P1N1 and N1P2, in addition to the latencies of the P1, N1, and P2 peaks, were analyzed. Our findings showed that P1, N1, and P2 latencies were considerably prolonged in the CE group compared to the Sh group. Furthermore, the amplitudes of P1N1 and N1P2 exhibited an increase in the CE group relative to the Sh group, a decline in the CE+ALCAR group in comparison to the CE group, and a subsequent return to normal levels. Finally, our results demonstrated that, at the dose and duration used here, ALCAR normalized the increased neuronal activity but had no effect on the conduction velocity of the hearing signal.